ChemInform Abstract: New in situ Trapping Metalations of Functionalized Arenes and Heteroarenes with TMPLi in the Presence of ZnCl2 and Other Metal Salts. Issue 3 (January 2015) - Frischmuth, Annette; Fernandez, Maitane; Barl, Nadja M.; Achrainer, Florian; Zipse, Hendrik; Berionni, Guillaume; Mayr, Herbert; Karaghiosoff, Konstantin; Knochel, Paul
Abstract Lithiation of an aromatic or heteroaromatic substrate is followed by transmetalation under different conditions.